Competencias digitales de los estudiantes de educación de la Universidad Nacional de Loja (Ciclo octubre, 2023/marzo, 2024) - Medina Calva, Marco Antonio (2024)
In the face of the accelerated technological development experienced by 21st-century digital society, teachers need to develop digital competencies related to the integration of educational technologies (ET), enabling innovation towards an active and interactive teaching-learning process (TLP). In this regard, the general objective was proposed: to evaluate the digital competencies of students at the National University of Loja (UNL), from October 2023 to March 2024 academic period. To carry out the study, a methodology with a quantitative approach, descriptive-explanatory scope, and non-experimental design corresponding to field research was used. The study population consisted of 220 students in the final cycle of teacher training, from the Faculty of Education, Art and Communication (FEAC) at UNL. The survey technique was employed through a questionnaire consisting of 4 dimensions, distributed among 22 descriptors and 4 levels of competency development: beginner, intermediate, expert, and transformative. Among the most relevant results, it was found that the majority of the student population ranges between 18 and 28 years old, with a notable predominance of females. Regarding the 4 dimensions, it is observed that students are positioned at level 1, with a slight tendency towards level 2 of acquired competence. This indicates that they possess the basic knowledge to generate good initial educational practices, as they use certain technological resources and tools, respect copyright in downloaded materials, have elementary notions of computer security, and have also participated in the Educational Technology (ET) workshop proposed by each program. In conclusion, the responsibility of UNL as an agent of change in the continuous improvement of TLPs is highlighted, emphasizing the importance of structured training plans for all cycles of teacher training, focusing on strengthening digital competencies. Keywords: Digital competence; teacher training; educational innovation; educational technologies; interactive learning.